Stories of Unionization: Four Teachers' Perspectives on Collective Bargaining in Two Canadian Private ESL Schools - Breshears, Sherry Diane (Simon Fraser University, 2008)
The private English language training industry in Canada has grown rapidly in recent years. While subject to influences of market competition, ESL schools have had little educational or labour regulation. This study presents life history interviews with four teachers who became involved in forming unions at their workplaces because of their experiences with just labour practices. The findings show that teachers sought union protection to deal with a pervasive sense of insecurity in their jobs. Through unions, they established clearer processes for dealing with such issues as the allocation of work and the resolution of grievances, a forum for communicating concerns to management, and a peer support structure. Additionally, these teachers have gained significant increases in salary and benefits. These narratives also show teachers, both individually and collectively, engaging in resistance as they confront the daily infringement of business priorities on their capacities to develop and practice as educators.

Watching Workers: A Critical Review of the Law Regarding Electronic Employee Monitoring in Non-Unionized Workplaces in Canada - Bueckert, Melanie R. (University of Manitoba, 2008)
This thesis addresses the topic of electronic employee monitoring in non-unionized workplaces in Canada. Electronic employee monitoring is defined as including (1) the use of electronic devices to review and evaluate employees’ performance; (2) ‘electronic surveillance’; and (3) employers’ use of computer forensics. Detailed consideration is given to a variety of technologies, including computer, internet and e-mail monitoring, location awareness technologies (such as global positioning systems and radio frequency identification), as well as biometrics, and the developing case law surrounding these innovations. Analogies are drawn to the jurisprudence developing with respect to unionized workplaces and under statutory unjust dismissal regimes. This analysis leads to the conclusion that legislative reform is necessary, either through(1) the creation of parallel private sector privacy regimes, such as those in British Columbia and Alberta, mirroring existing federal legislation; (2) amendments to existing employment standards legislation; or (3) the enactment of a stand-alone surveillance statute.

Commissioning Consent: An Investigation of the Royal Commission on the Relations of Labour and Capital, 1886-1889 - Cole, Stephen J. (Queen's University, 2008)
The 1880s were turbulent years in the Dominion. Under the auspices of the National Policy, Canada was in the midst of a social and political ‘transformation.’ The social and cultural aspects of this transformation became a source of public debate as the ‘Labour Question’ and the relations between labour and capital reached a high mark of political and economic significance. Waves of strikes and the emergence of large international labour organizations challenged many liberal Victorian ideas about a strictly limited state. Many looked upon the federal government as responsible not only for economic growth, but also for protection from the more pressing problems of industrial life. The Royal Commission on the Relations of Capital and Labour is a testament to not only the turbulent economic relations in late-Victorian Canada, but the emergence of the Canadian state’s active role in social relations. Its very title envisioned a dual role for the Canadian state: to “promote the material, social, intellectual and moral prosperity” of labouring men and women, and to improve and develop “the productive industries of the Dominion so as to advance and improve the trade and commerce of Canada.” However, this thesis argues that the Labour Commission was more subtly designed to enhance the prestige of the Canadian state and install Ottawa as an authority on, and mediator of, industrial relations in Canada. Attention to the formation, activities, and impact of the Labour Commission suggests that, rather than an exercise in addressing a mounting social polarization between “labour” and “capital,” the Commission lends insight into the emergence of a Canadian middle class. It was a carefully-constructed exercise in the assertion of middle-class cultural hegemony whereby such values and understandings as respectability, morality, manliness, worth and expertise were naturalized. In the process, the tension between labour and capital was diminished and in its place were developed visions of social reciprocity and mutual interest. It is in this way that the Labour Commission was an exercise in ‘commissioning consent:’ it placed oppositional voices and wrenching exposés about industrial life in a framework that worked to quell rather than stimulate far-reaching critiques of the established order. The Commission’s formation, methodology and language functioned like an industrial exhibition rather than a pointed social investigation. The evidence presents a thriving economy that had grown exponentially under a wise and paternal government. It also presented a vision of the Dominion whereby the disturbances that occurred between labour and capital could be handled within a conventional language of liberal politics. In addition, social and intellectual elites were fully ensconced in the formation and legitimization of these social and moral understandings. Because it was up to the state to select who would speak for labour and capital, the Commission’s message was not one of class polarization. Thus, exploring who became ‘labour’ and who ‘capital,’ and what sorts of things they said to each other, sheds light on to the emergent strategies of the Canadian state as it sought to understand and influence civil society. The Commission is an indication, even anticipation, of a more activist and energetic state.

Precariousness on the Menu: Restaurant Work and Labour Mobility Within the Low-Wage Service Industry in Kingston, Ontario - Denstedt, Mark James (Queen's University, 2008)
Precarious employment refers to forms of work characterized by limited job security, few employment benefits, lack of control over the labour process and low-wages. Restaurant work demonstrates a range of precarious forms of employment and reveals the complexity of issues that such jobs raise in the context of the regulation of the local labour market. This thesis analyses the nature of precarious employment in the restaurant industry in Kingston, Ontario. In particular, it seeks to understand how precarious employment is shaped by the structure and dynamics of the local labour market. The research highlights the role played by labour mobility, in shaping workers’ experiences of precarious work. Labour mobility refers to the movement of workers between different jobs and between different worksites within a structured local labour market as they seek to better their economic situation and generate a sustainable income for themselves. Through a discussion of labour mobility, this thesis seeks to contribute to a new lens through which the impacts of a precarious and flexible labour market can be better understood as they shape the lives of workers themselves. The objective of this study is to better understand the factors which shape the lived realities of precarious restaurant workers in one specific local labour market. The empirical analysis draws on data collected by Statistics Canada and interviews conducted with both employers and employees in local restaurants to analyze the structure of the local labour market and the nature of precarious employment. The research demonstrates that the restaurant industry in Kingston is comprised of three distinct submarkets, each of which appears to operate largely independently of one another. Interviews were conducted with employees and employers in the submarket located in downtown Kingston. Within this submarket the combined processes of labour market segmentation and labour mobility has a significant impact on workers experiences of precarious employment. By understanding the complex interaction of these two features within the labour market, we can begin to conceive of ways to address the issues associated with the precariously employed in the low-wage service industry.

A Crisis of Social Democracy: Organized Labour and the NDP in an Era of Neoliberalism - Fowler, Tim (Brock University, 2008)
The NDP was founded out of the ashes of the Co-Operative Commonwealth Federation to cooperate with the Canadian Labour Congress to become the 'political arm of organized labour' in Canada. The NDP has long claimed they are the party which represents the policy goals of organized labour in Canada: that the NDP alone will fight for trade union rights, and will fight for Canadian workers. Divergent Paths is an examination of the links between the labour movement and the NDP in an era ofneo-liberalism. Provincial NDP governments have become increasingly neoliberal in their ideological orientation, and have often proved to be no friend to the labour movement when they hold office. The Federal party has never held power, nor have they ever formed the Official Opposition. This thesis charts the progress of the federal NDP as they become more neoliberal from 1988 to 2006, and shows how this trend effects the links between the NDP and labour. Divergent Paths studies each federal election from 1988 to 2006, looking at the interactions between Labour and the NDP during these elections. Elections provide critical junctions to study discourse - party platforms, speeches, and other official documents can be used to examine discourse. Extensive newspaper searches were used to follow campaign events and policy speeches. Studying the party's discourse can be used to determine the ideological orientation of the party itself: the fact that the party's discourse has become neoliberal is a sure sign that the party itself is neoliberal. The NDP continues to drive towards the centre of the political spectrum in an attempt to gain multi-class support. The NDP seems more interested in gaining seats at any cost, rather then promoting the agenda of Labour. As the party attempts to open up to more multi-class support, Labour becomes increasingly marginalised in the party. A rift which arguably started well before the 1988 election was exacerbated during that election; labour encouraged the NDP to campaign solely on the issue of Free Trade, and the NDP did not. The 1993 election saw the rift between the two grow even further as the Federal NDP suffered major blowbacks from the actions of the Ontario NDP. The 1997 and 2000 elections saw the NDP make a deliberate move to the centre of the political spectrum which increasingly marginalised labour. In the 2004 election, Jack Layton made no attempt to move the party back to the left; and in 2006 the link between labour and the NDP was perhaps irreparably damaged when the CAW endorsed the Liberal party in a strategic voting strategy, and the CLC did not endorse the NDP. The NDP is no longer a reliable ally of organized labour. The Canadian labour movement must decide whether the NDP can be 'salvaged' or if the labour movement should end their alliance with the NDP and engage in a new political project.
Keywords: Social sciences

Racialized Immigrants In Canada’s Changing Labour Market: An Investigation Of The Effects Of Precarious Work On Black Caribbean Women - Hibbert, Maqueita (Ryerson University, 2008)
This research undertakes an examination of the employment opportunities and experiences of black Caribbean women in Canada, particularly within the context of the growing trend towards precarious jobs—casual, part-time and low paying—in the restructured Canadian labour market. The specific purview of this study is the labour history and employment experience of a representative group of black Caribbean women who work as Personal Support Workers in nursing homes across the Greater Toronto Area. A main concern of the study is to understand the ways in which precarious work affects these women’s settlement and integration experiences, particularly their ability to gain economic independence; this, in turn, affects a number of variables related to their, and others, perception regarding their status and place in Canada. By focusing on the case of Personal Support Workers, the study aims to shed light not only on the employment experiences of black Caribbean women in this sector but also to examine more closely the policies and employment practices that create labour market “niches” or labour “segregation” along racial and gender lines.

The Homeless and Reformers: Negotiating Progress in the Upper Streets of Halifax, 1890–1914 - Hood, David (Carleton University, 2008)
The extremely poor have often been cast as deviants or others, in both the past and the present. Historians of Atlantic Canada have used the idea of deviance as an acceptable approach to the poor and homeless of the past and tacitly encourage us to see the contemporary homeless as deviants. Victorian theorists such as Malthus and Mayhew pejoratively characterized the poor as an underclass. Contemporary writers have provided evidence that challenges the use of the concept in Canada. But it remains a powerful force within American sociology, which is able to cast its influence over Canadian historical writing. It is the contention of this research that it is possible to be true to the past, to reflect the warts and downfalls of the extremely poor and homeless who lived there, but at the same time recognize their efforts to follow prevailing norms and to empathize with their plight and in doing so generate at least the possibility of recognition and empathy in the present. Such recognition and empathy may be the keys to creating and maintaining humane solutions to poverty and homelessness. The examinations conducted by this research address an area of our past that has been largely overlooked. This research supplements broad historical surveys of social welfare legislation by examining social welfare policy in action at the local level. By positioning itself at the convergence of labour history and studies of poverty, and by demonstrating that the populations examined by these discrete areas of research are more alike than different, this research shows that labour history can be extended to include many of those who lived "rough" in the past. Through its approach this research hopes to encourage a view that can help to integrate the study of extreme poverty and homelessness into the mainstream of Canadian historiography.
Keywords: Halifax; Homeless; Nova Scotia; Progress; Reformers; Social sciences

When Red Meets Green: Perceptions of Environmental Change in the B.C. Communist Left, 1937-1978 - Martin, Eryk (University of Victoria, 2008)
From the 1940s to the 1970s the communist left in British Columbia used debates and perceptions of environmental change as a means to engage in a critique of capitalist society. In engaging in these debates, communists articulated a Marxist understanding of the connections between capitalism and environmental change. However, these articulations were heavily connected to broader occurrences that situated the communist left alongside a diverse group of social actors. Beginning in the 1940s the communist left situated their critique of provincial forest policy into a wider social debate over the management of forest resources. During the 1950s and 1960s, concerns over environmental change were transformed into debates over the effects of nuclear weapons and industrial pollution. From the late 1960s through to late 1970s elements of the communist left once again engaged with the environmental changes taking place in the forest sector, as renewed concerns developed over the status of the forest economy and the preservation of wilderness areas. To investigate the communist left’s perceptions and politicization of these issues this thesis focuses on the activities of communist controlled unions such as the International Woodworkers of America as well as the B.C. section of the Communist Party of Canada/Labour Progressive Party. In addition to these organizations, this thesis also follows the experiences of Erni Knott. As a woodworker, a founding member of the IWA, a member of the Communist Party, and an active environmentalist, Knott’s experiences highlight the complex way in which communist politics merged and conflicted with perceptions of environmental change.

Rural Businesses on Vancouver Island: Challenges and Opportunities - Siemens, Lynne Marie (University of Hertfordshire, 2008)
Many rural areas are undergoing structural changes as jobs in forestry, fishing, mining, agricultural and other natural resource-based industries decline. These communities, often based around these industries, are generally small and located some distance from urban areas. They are faced with decreasing population as residents and their families leave for jobs elsewhere. As a result, the communities and residents are looking for alternative ways to create employment and sustain themselves. Given the nature of these rural locations, many small businesses based there face challenges that are not generally experienced by enterprises in urban areas. Some communities are not accessible by paved road while others are not accessible by road at all, relying instead on water and air transportation. The business people in these areas often operate without standard business infrastructure, which can include telephone lines, broadband Internet, banking services and other items, and can have difficulty accessing supplies, customers, employees and other required materials. However, there has been relatively little research on the challenges facing rural businesses and the specific methods by which these owners mitigate these challenges. Understanding and addressing the challenges faced by these businesses becomes important in order to support and encourage economic growth and development in these rural communities. Building on this context, this research looks to answer the following questions: • Why do people start businesses in rural locations? • What type of businesses do they start? • What challenges do these rural businesses face? • How do owners respond to these challenges? Vancouver Island and the surrounding smaller islands in British Columbia, Canada serve as the research site. Given the exploratory nature of this research, an inductive approach has been selected with the use of case studies, interviews and grounded theory analysis. Purposeful sampling is used with the sample businesses meeting specific criteria, based on location, business size and definition of success. These businesses are interviewed at their locations to allow the researcher to experience the challenges associated with accessing the particular rural community. The interview topics are focused on the above research questions. There are several common characteristics among the sample owners and their businesses. The owners tend to be in-migrants who moved to the rural area for lifestyle reasons. They have started their business to provide an income, take advantage of a business opportunity, or both. Family members, particularly spouses, are actively involved in the business. In many cases, participants supplement their business income with other income sources to ensure business viability. Success is measured generally by personal and lifestyle goals, rather than financial criteria. The businesses face common challenges in terms of a limited local population base which impacts on market size and labour pool, rural location and access to urban centres, gaps in business and social services infrastructure and heavy time demands. The owners respond to these challenges in a variety of ways which includes the involvement of family, core business diversification, alternative income sources, long hours invested in the business and involvement with the community. To meet these challenges and devise their responses, the owners draw upon four key resources – their own skills and attitudes, their family, business and community. The resulting conceptual framework draws together these key resources and suggests that all four must be present to ensure success within a rural context. Each resource is comprised of several components which contribute to business success. The framework also integrates several resource-based theories, which consider the key resources either separately or in pairs, to create a holistic model. The conclusions focus on several key areas. This research contributes to the knowledge base on rural small businesses by creating a framework that draws directly from the experience of these owners and their objectives and motivations for their businesses. It reflects their internal focus and a concentration of the four resources that they access easily from within their domain. This research also suggests some possible roles for government which focus on its role in shaping the larger environment, particularly at the infrastructure level and human capital development. Finally, future research directions are recommended. This study considers a relatively unexplored topic and suggests ways for rural small businesses to address the challenges which they face. With this knowledge, individuals, businesses, communities and other interested organizations can work to achieve their economic development goals.

Les travailleurs miniers de l'Abitibi-Témiscamingue : la main-d'oeuvre de la mine Lamaque, 1948-1985 - Simard, David (Université de Montréal, 2008)
Ce mémoire porte sur les travailleurs de la mine Lamaque entre 1948 et 1985. À partir d’une étude approfondie des fichiers d’employés de l’entreprise, qui est l’une des plus riches mines d’or de l’histoire du Québec, nous analysons l’évolution de la main- d’œuvre sous les volets de la composition ethnique, de l’expérience dans le secteur minier ainsi que de la mobilité. Notre enquête révèle l’existence de deux périodes-clés autour desquelles on assiste à une transformation rapide de la main-d’œuvre: la période 1948-1960 est le théâtre d’un important processus d’homogénéisation des effectifs alors que les années 1967-1977 sont la scène d’un double processus de sédentarisation et de qualification de la main-d’œuvre. D’un groupe de travailleurs cosmopolites, peu expérimentés et très mobiles, il en ressort, au sortir de ces années, une main-d’œuvre nettement plus expérimentée, plus sédentaire et composée presque exclusivement de travailleurs canadien-français et, de surcroît, témiscabitibiens. Au-delà de ces transformations, notre mémoire comporte un bref aperçu de l’histoire de l’industrie aurifère québécoise et de la mine Lamaque, du « boom minier » des années 1930 à la grande relance de l’industrie au début des années 1980. De plus, nous portons une attention particulière aux travailleurs d’origine européenne qui forment, jusqu’à la fin des années 1960, une proportion appréciable de la main-d’œuvre. En plus de lever le voile sur la composition de ce groupe de travailleurs, notre étude révèle des similitudes insoupçonnées entre le contingent européen et canadien-français.
https://doi.org/1866/7681

Co-Opting Precariousness: Can Worker Cooperatives Be Alternatives to Precarious Employment for Marginalized Populations? A Case Study of Immigrant and Refugee Worker Cooperatives in Canada - Wilson, Amanda (McMaster University, 2008)
This thesis is an exploration into the potential for worker cooperatives to be conceptualized and experienced as an alternative to precarious employment for immigrants and refugees. It argues that current analysis and responses to precarious employment fail to fully address the root causes of precarious employment and fail to suggest what forms of alternative employment relations we should be striving to build. It is argued that by tracing the roots of precarious employment to the organization of work, the worker cooperative model can be seen as a potential solution to these root problems. This hypothesis is explored through two case studies of immigrant worker cooperatives, analyzing the employment experiences of several of its members. It concludes that workers cooperatives appear to provide alternatives in the areas of control, security and social capital and empowerment. However, more work is needed to support and facilitate the development and sustainability of cooperatives in order to improve in the areas of wages and formal benefits. Despite the challenges of worker cooperatives, the author argues that they remain an important tool, invoking a politics of the act that seeks to build alternative spaces of employment without relying on government or employers.

Workability of Intergovernmental Administrative Relations: A Comparison of Labour Market Policy in Post-Devolution Canada and the United Kingdom - Wood, Donna (University of Edinburgh, 2008)
This is a comparative study of intergovernmental relations in labour market policy in Canada and the United Kingdom (UK) between 1996 and 2006, the first phase of devolution in each country. The study focuses primarily on relations between the central government and a single sub-state in each country (Alberta in Canada and Scotland in the UK) and addresses three research questions: 1) to what extent were there differences in intergovernmental relations between the countries?2) what accounted for these differences? 3) what impact did these differences have on the character and workability of the intergovernmental relations system in each country? Workability was assessed based upon the degree to which trust ties developed between senior officials. The analysis concludes that the structure of the state, the structure of the policy domain, and the presence of two important accommodation mechanisms in the UK not found in Canada (the party system and the civil service) made intergovernmental relations in labour market policy in the two countries fundamentally different. In Canada, intergovernmental relations were multilateral, interprovincial and bilateral, whereas in the United Kingdom they were only bilateral. Despite devolution, the UK Government retained control of most policy levers, whereas in Canada devolution has limited federal control and influence and any notion of a national labour market system. Trust ties were enhanced by consistency between the key players, routinized engagement, reliability, honesty, respect, capacity and willingness to engage, and transparency. Although shared objectives made engagement easier, they were not a prerequisite for a positive relationship. Bilateral relationships that took place within the geographic boundaries of Alberta and Scotland were considered as positive and highly workable. Difficulties arose when relationships became multilateral or bilateral relations were managed at a distance. Despite devolution, multilateral relations in the historically conflicted labour market policy domain in Canada remained competitive, with a low degree of workability. Relationships with respect to disability and immigration issues were more positive. In the UK relationships in the welfare to work policy area were cooperative and highly workable. Relationships in skills and immigration did not fare as positively.

Skilled Trades' Work and Apprentice Training in the Manufacturing Industry with a Primary Focus on the Millwright Trade: An Inter-Generational Study - Wren, John Charles (University of Toronto, Ontario Institute for Studies in Education, 2008)
Technology has enabled management to utilize automation in the methods of production, and as such promoted a reduction in the use of traditional skills for traditional skilled trades' workers while narrower task specific apprenticeship training programmes promote the loss of trade knowledge traditionally passed from a trades' person to an apprentice in the manufacturing industry. The purpose of this intergenerational study is to trace the changing skill requirements affected by developing technologies in the manufacturing process focusing on the traditional skills of millwright trade, and associated skilled trades. To place in context the origins of the skilled trades' I have included brief histories of five skilled trades, to represent a selection of skilled trades' often closely connected through their work in the manufacturing industry; the millwright, electrician, welder, toolmaker and machinist. In an effort to also report the possible effects of technology on skilled trade labour from a tradesperson's perspective I have utilised my own experiences and incorporated anecdotal evidence from interviews with certified millwrights and apprentices that are either presently working in the trade, or have retired from the trade in Canada. Interviews with three generations of millwrights assisted in making comparisons of training and expectations of millwright work, together with changes in the control millwrights' exercise over the jobs they perform. The focus of the thesis is the possible effects of technological progress on the required skill sets of three generations skilled trades' with a primary focus on millwright skilled trades'. Restructuring and the utilization of new technologies has facilitated a reduction in the overall number of skilled trades' workers that were previously required when traditional skilled trades' personnel were utilised. Therefore, utilization of technology to lower production costs by modern industry is affecting social structure, in that, traditional opportunities for members of the working class, without the benefit of a university education, are restricted in their ability to obtain well paid jobs as skilled trades' personnel in the manufacturing industry. Thesis: Technology has enabled automation to be utilized by management in the methods of production, and as such promoted a reduction in discretion and control in the use of traditional skills for traditional skilled trades' workers while narrower task specific apprenticeship training programmes promote the loss of trade knowledge traditionally passed from a trades' person to an apprentice in the manufacturing industry.
Keywords: Apprentice training; Education; Manufacturing; Millwright; Skilled trades

La perception de la fête internationale des travailleurs dans les journaux canadiens entre 1906 et 1945 - Zombecki, François (Université du Québec à Montréal, 2008)
Le 1er mai 1906, les membres d'un éphémère parti socialiste canadien organisent à Montréal la première célébration de la fête internationale des travailleurs. Des centaines de personnes y défilent sous le drapeau rouge. L'événement se répète ensuite presque chaque année, et s'étend à la plupart des grandes villes du pays. L'histoire du mouvement socialiste / communiste au Canada et au Québec a certes été écrite, mais l'historiographie délaisse le sujet de sa fête annuelle. Pourtant, les journaux canadiens ont couvert l'événement, année après année, léguant aux générations suivantes une riche couverture. Celle-ci représente un outil utile, bien qu'imparfait, pour mieux saisir l'opinion de la population de l'époque à l'endroit des communistes. La présente recherche analyse plus de 400 articles de grands quotidiens pour sonder la perception des Canadiens, durant la première moitié du XXe siècle, quant au phénomène de la fête du 1er mai et au mouvement socialiste / communiste qui l'anime. Dans un premier temps, nos recherches présentent la couverture des journaux de plusieurs grandes villes canadiennes. Nous constatons alors d'importantes différences entre la perception des Canadiens français et celle des Canadiens anglais au Québec. Nous découvrons également une affinité particulière à Winnipeg -et même à Vancouver, dans une moindre mesure -pour le mouvement et sa fête. Le facteur ethnique explique en bonne partie tant les affinités de certaines communautés pour le mouvement, que la répulsion des Canadiens français. Dans un deuxième temps, à travers une approche chronologique plutôt que régionale, des facteurs conjoncturels et internationaux expliquent les fluctuations dans le ton des journaux entre 1906 et 1945. Ce travail de recherche jette la lumière sur une fête particulière, exclue du calendrier officiel nord américain et pourtant observée à travers la majeure partie du monde occidental. L'analyse de la couverture journalistique de l'événement permet de tirer d'intéressantes conclusions quant à la façon dont a été perçu le mouvement communiste canadien, au moment de son apogée.